Analyzing the Word Formation of Slang Vocabulary Employed by Fathia Izzati on YouTube - Fadhillah, Nurul; Nurweni, Ari (Abjadia : International Journal of Education, 2023)
Slang is a form of language, expressions, or specialized language usage commonly found in informal conversations, particularly within specific groups. Fathia Izzati, known as "kittendust," is a YouTube content creator with 695,000 subscribers. In her YouTube account, Fathia uploads videos related to English language learning terms in daily life, often incorporating slang words. This research aims to comprehend the meanings and processes of word formation in slang used by Fathia Izzati in her videos. The research methodology is descriptive qualitative, referencing George Yule's (2010) theories on slang word formation processes. Data were obtained from 15 videos uploaded by Fathia Izzati between November 2021 and December 2022. The findings reveal that out of Yule's ten slang and word formation theories, only five are reflected in the analyzed videos. Blending emerges as the most common method for creating new words, constituting 39.24% of all new terms. Other prevalent methods include doubling (34.18%) and halving (18.99%). Clipping accounts for 5.06%, while acronyms are the least common, comprising only 2.53%. This research provides insights into the use of slang by Fathia Izzati within the context of English language learning on YouTube.